Upaya Pembelajaran Membaca Notasi Angka Lagu Indonesia Subur pada Siswa-Siswi Kelas VIII SMP Negeri X Kupang - Tefa, Magdalena Vamilia; Elu, Agustinus; Kaet, Margareta (Universitas Jambi, 2025)
The problem experienced in SMP Negeri X Kupang is that students have difficulty when targeting notes that have increasingly distant intervals. Thus, the researcher is motivated to conduct research on Learning Efforts to Read Numeric Notation in the Song Indonesia Subur for Class VIII Students of SMP Negeri X Kupang. The formulation of the problem in this study is How is the Learning Process of Reading Numeric Notation in the Song Indonesia Subur for Class VIII Students of SMP Negeri X Kupang? And What are the difficulties experienced by class VIII students of SMP Negeri X Kupang in reading numeral notation? The purpose of this study was to determine the learning process of Reading Numeric Notation in the song Indonesia Subur for class VIII students of SMP Negeri X Kupang and to determine the difficulties experienced by class VIII students of SMP Negeri X Kupang in reading notation. The implementation of this learning process obtained evaluation results with 20 students who were very good because the ability to read numeral notation from students increased significantly after participating in learning to read numeral notation. At the first meeting 15% of students were able to read the notation well, 25% of students read the notation with minor errors, and 60% of students were unable to read the notation while at the last meeting 75% of students were able to read the notation well, 25% of students read the notation with minor errors. So based on the results of the study it can be concluded that the ability of students in addition to musicality factors is also the motivation to learn in class, and the learning methods provided.